Microplastic mediated arsenic toxicity involves differential bioavailability of arsenic and modulated uptake in rice (Oryza sativa L.) - Yueyi Wu; Chaorui Yan; Jianying Shang; Zhaoyong Zeng; Yuanfeng Huo; Deqiang Li; Yinggang Xu; Xin Xian; Yang Li; Xuesong Gao; Fu Huang; Guangdeng Chen (Ecotoxicology and Environmental Safety)
Microplastics (MPs) and arsenic (As) commonly co-expose in agricultural systems, posing a significant threat to crop growth. This research investigated the combined effects of polyethylene (PE)/ polylactic acid (PLA) with As on growth characteristics, As accumulation, and microbial communities in two genotypes of rice. The results showed that MPs with As exhibited antagonistic effects at low As concentrations, while co-exposure with high As concentrations showed synergistic toxicity in two genotypes of rice. The compound toxicity induced by co-exposure to high As-accumulating rice was more severe. And PE exhibited a stronger impact on rice growth, As absorption and translocation, as well as oxidative stress damage compared to PLA. At 30 mg kg−1 As concentration, PE and PLA decreased the As content in rice roots by 61.61–77.65 mg kg−1 and 91.63–98.22 mg kg−1, respectively, Whereas PE and PLA significantly increased the As in roots at high As concentration. Because MPs competed with rice roots for As adsorption, they altered As bioavailability and the iron plaque content under low As exposure, thereby reducing As toxicity to rice. In contrast, co-exposure of MPs with high As caused irreversible damage to the oxidative stress system, with reduced iron plaque and increased in As bioavailability, greatly exacerbate As toxicity to rice. In addition, MPs altered soil enzyme and microbial communities in response to co-exposure. These findings provide critical insights into the comprehensive toxicity of As and MPs (traditional/biodegradable) to the soil-plant system.